Effect of Different Percentages of Titanium Dioxide Additives on the Enamel Protecting of Steel Surface - Saeed, Ghazi; Alnamie, Ibtihal; Abdual Noor, Sabah (Iraqi Journal of Science, 2023)
This work involves the development of ceramic coating to steel surfaces (enamel).This enamel high quality consisted of two ceramic layers to ensure excellent bonding with the steel surfaces. The first is called the ground coat which proved bonding between the steel base and the second outer layer called the cover coat. Various concentrations of TiO2 were separately added to the mixture of the cover coat, resulting in to much better densification of the ceramic outer layer, the hardness, thermal shock resistances, and glossiness were improved also .Moreover this addition has raised the corrosion resistances of the ceramic in harsh acidic environment and at higher temperatures Also this enamel was used to protect the surfaces of steels which have various carbon content.